Study of Benzofuroquinolinium Derivatives as a New Class of Potent Antibacterial Agent and the Mode of Inhibition Targeting FtsZ - Zheng, Yuan-Yuan; Du, Ruo-Lan; Cai, Sen-Yuan; Liu, Zhi-Hua; Fang, Zhi-Yuan; Liu, Ting; So, Lok-Yan; Lu, Yu-Jing; Sun, Ning; Wong, Kwok-Yin (Frontiers in Microbiology, 2018)
New generation of antibacterial agents are urgently needed in order to fight the emergence of multidrug-resistant bacteria. FtsZ is currently identified as a promising target for new types of antimicrobial compounds development because of its conservative characteristics and its essential role played in bacterial cell division. In the present study, the antibacterial activity of a series of benzofuroquinolinium derivatives was investigated. The results show that the compounds possess potent antibacterial activity against drug resistant pathogens including MRSA, VREF and NDM-1 E. coli. Biological studies reveal that the compound is an effective inhibitor that is able to suppress FtsZ polymerization and GTPase activity and thus stopping the cell division and causing cell death. More importantly, this series of compounds shows low cytotoxicity on mammalian cells and therefore they could be new chemotypes for the development of new antibacterial agents targeting the cell-division protein FtsZ.